Evaluation Of Distance Learning Program For Elementary School Students In Banyudono Village, Boyolali Post Pandemic - Darmanto Minggele (Insight School Academy, 2024)
Background: During the pandemic, the world of education has undergone significant changes, especially in the educational strategies implemented. One of the strategies in the world of education is the existence of a distance learning model. Purpose: This study aims to evaluate the implementation of distance learning at the beginning of the planning process, implementation, learning outcomes and obstacles faced. Design/methods/approach: The data sources in this quantitative research are teachers and principals totaling fourteen people. The technique of selecting research subjects used purposive sampling. sampling . Data collection using interviews and documentation with interview guide instruments. Data analysis techniques in this study are data reduction, data presentation, and drawing conclusions . Findings: Interview data and documentation analyzed descriptively show that the evaluation of the implementation of distance learning (PJJ) has generally met the standard criteria set by the government. However, the evaluation of learning outcome measurements is still less effective due to the obstacles faced in measuring students' actual abilities. One of the obstacles faced in implementing this distance learning is that student learning outcomes are not purely what students do. Research implications/limitations: Some students get results because of the help of parents or other parties in working on the questions, another deficiency faced in this study is that the learning media used in the form of online applications cannot be an ideal learning tool like face-to-face learning. Originality/value: It is hoped that other research that will be conducted in the future will be able to add more complete knowledge related to similar research themes.